Gratitude Therapy in Chronic Low Self-Esteem in Schizophrenia Patients: Case Study - Aflahatinufus, Azka; Hidayati, Nur Oktavia; Hendrawati, Hendrawati (Universitas Pendidikan Indonesia, 2023)
Schizophrenia can cause negative symptoms such as delusions, hallucinations, disorganized speech or behavior, and impaired cognitive abilities. So that many people with schizophrenia get stigma from their families and society. This makes people with schizophrenia experience chronic low self-esteem, that is, they feel they are worthless and do not have any talents or abilities. One of the non-pharmacological therapies to reduce chronic low self-esteem is gratitude therapy. The purpose of writing this case study is to illustrate the giving of gratitude therapy to chronic low self-esteem in schizophrenic patients. This research uses a sample of patients who are being treated at a mental rehabilitation house. The patient in this case study was diagnosed with paranoid schizophrenia and experienced chronic low self-esteem, characterized by patients who are difficult to communicate with and say they are worthless. This study used a case study descriptive method in patients with schizophrenia with chronic low self-esteem. After being given the gratitude therapy intervention for 5 days and interspersed with several interventions, namely yoga and butterfly hugs, the patient seemed to be more cheerful and active. This is evidenced by the patient looking willing and inviting other people to communicate, and starting to be confident to appear in front of others. Gratitude therapy can reduce chronic low self-esteem in schizophrenic patients. Therefore, giving gratitude therapy interventions is recommended for health workers, especially the psychiatric nursing team as a non-pharmacological intervention in reducing chronic low self-esteem in schizophrenic patients. Suggestions for further research, so that you can apply gratitude therapy interventions with more samples and carry out follow-ups in sufficient time. So it is hoped that in the future more and more nurses will use gratitude therapy interventions as evidence-based practice to overcome chronic low self-esteem in patients with mental health problems.